2008
DOI: 10.1007/s11195-008-9091-y
|View full text |Cite
|
Sign up to set email alerts
|

Adjustment to Changes in Sexual Functioning Following Spinal Cord Injury: The Contribution of Men’s Adherence to Scripts for Sexual Potency

Abstract: Recent epidemiological statistics suggest approximately 250,000 people in the United States live with a spinal cord injury. Men constitute roughly 82% of these individuals. Following spinal cord injury, men frequently experience significant changes in their sexual functioning. As a result, men with spinal cord injuries are at an increased risk for experiencing adjustment difficulties. Unfortunately, relatively little is known about factors that promote or impede men's adjustment to these changes. In the presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 49 publications
2
13
0
Order By: Relevance
“…Former studies have shown that foreplay plays an important role in the sex life of men with SCI: hugging, kissing, caressing, oral sex, visual aids or fantasy are commonly practiced. However, in those studies, foreplay was mainly practiced or encouraged as a substitute for intercourse [6,7,9,[22][23][24][25]. This study confirmed that the majority of men enjoyed lengthy foreplay, and that it increased their arousal.…”
Section: Foreplay Intercourse and Desiresupporting
confidence: 56%
See 2 more Smart Citations
“…Former studies have shown that foreplay plays an important role in the sex life of men with SCI: hugging, kissing, caressing, oral sex, visual aids or fantasy are commonly practiced. However, in those studies, foreplay was mainly practiced or encouraged as a substitute for intercourse [6,7,9,[22][23][24][25]. This study confirmed that the majority of men enjoyed lengthy foreplay, and that it increased their arousal.…”
Section: Foreplay Intercourse and Desiresupporting
confidence: 56%
“…Most had chosen a partner after the SCI with whom they seemed to have developed open communication regarding their sexuality. Most importantly, they developed other aspects of sexuality such as intimacy and emotional sharing, which are major components of the adaptation to their new sexual lives, as has been shown in other studies [7,11,15,16,22,26,40,43]. It has also been found that living with a stable partner in an enduring relationship [10,13,15,16] or having multiple partners [6] increases sexual satisfaction.…”
Section: Sexual Satisfactionmentioning
confidence: 55%
See 1 more Smart Citation
“…It has also been reported that men in particular experience significant changes in their sexual functioning following a spinal cord injury. Burns et al ., (2008a)[ 9 ] reported that of the 250,000 people in the United States with a spinal cord injury, men constitute roughly 82% of this population. While changes in sexual functioning following a spinal cord injury pose a serious threat to men's sense of masculinity, little is known about the factors that promote or impede adjustment to these changes.…”
Section: Thematic Findingsmentioning
confidence: 99%
“…The adjustment difficulties these men experience may also be a function of the degree to which they conform to traditional masculine norms (Burns et al 2008;Tepper 1999). Specifically, adherence to masculine norms stressing the importance of men's sexual prowess in defining their worth may exacerbate their adjustment by enhancing the salience of post-injury changes in sexuality .…”
Section: Men's Sexuality and Depression Following Spinal Cord Injurymentioning
confidence: 99%